The transcription factor Foxo1 controls germinal center B cell proliferation in response to T cell help - Inoue, Takeshi (J Exp Med, 2017)
Germinal center (GC) B cells cycle between two states, the light zone (LZ) and the dark zone (DZ), and in the latter they proliferate and hypermutate their immunoglobulin genes. How this functional transition takes place is still controversial. In this study, we demonstrate that ablation of Foxo1 after GC development led to the loss of the DZ GC B cells and disruption of the GC architecture, which is consistent with recent studies. Mechanistically, even upon provision of adequate T cell help, Foxo1-deficient GC B cells showed less proliferative expansion than controls. Moreover, we found that the transcription factor BATF was transiently induced in LZ GC B cells in a Foxo1-dependent manner and that deletion of BATF similarly led to GC disruption. Thus, our results are consistent with a model where the switch from the LZ to the DZ is triggered after receipt of T cell help, and suggest that Foxo1-mediated BATF up-regulation is at least partly involved in this switch.